Pemanfaatan Kotoran Sapi menjadi Pupuk Organik Sebagai Bentuk Implementasi Hukum Lingkungan dalam Perlindungan Alam - Brik Kumala; Lu’lu’iyyatul Fikriyah; Ella Suhaela Syahla; Puji Lestari (TAAWUN, 2023)
The lack of knowledge, both theoretically and practically, regarding the benefits, functions and methods of making organic fertilizers made most of the residents of Jejel village, Lamongan district use chemical fertilizers or inorganic fertilizers as the main ingredients to increase their agricultural yields. Communities/farmers do not really understand that in the long term the use of inorganic fertilizers will erode nutrients and various important minerals in the soil, causing the soil to become less fertile and in the end this will result in minimal crop yields and even crop failure. Residents complain about the high price of inorganic fertilizers in the market so that the profits generated by residents from agricultural products are smaller and not sufficient to support the economy of farmers in general. Based on the above data, which the author obtained through direct observation and interviews with residents of Jejel village, the author took the initiative to conduct counseling and training on how to make organic fertilizer from cow dung using the main ingredient EM-4 plus other materials around the residents. The choice of cow manure as an alternative to making organic fertilizer is due to the fact that the average resident keeps cows as livestock. This service activity starts from the socialization stage, ensuring the availability of the main ingredients and media for making fertilizer to direct practice with residents. As a result, residents then began to be aware of the benefits of organic fertilizers and the dangers of inorganic fertilizers. Residents also finally realized that the use of organic fertilizers is more cost-effective and interested in starting to use cow manure as a soil fertilizer to replace inorganic fertilizers.